Structure‐Based Design of Fluorogenic Substrates Selective for Human Proteasome Subunits - Maurits, Elmer (Chembiochem, 2020)
Proteasomes are established therapeutic targets for hematological cancers and promising targets for autoimmune diseases. In the past, we have designed and synthesized mechanism‐based proteasome inhibitors that are selective for the individual catalytic activities of human constitutive proteasomes and immunoproteasomes: β1c, β1i, β2c, β2i, β5c and β5i. We show here that by taking the oligopeptide recognition element and substituting the electrophile for a fluorogenic leaving group, fluorogenic substrates are obtained that report on the proteasome catalytic activity also targeted by the parent inhibitor. Though not generally applicable (β5c and β2i substrates showing low activity), effective fluorogenic substrates reporting on the individual activity of β1c, β1i, β2c and β5i subunits in Raji (human B cell) lysates and purified 20S proteasome were identified in this manner. Our work thus adds to the expanding proteasome research toolbox through the identification of new and/or more effective subunit‐selective fluorogenic substrates.